Reconstruction of Distal Radius Osteochondral Defects Using Metatarsal Autografts: a Multi-case Series - Goon, Patrick K.Y.; Stougie, Shirley D.; Vaghela, Kalpesh R.; Coert, J. Henk (Revista Iberoamericana de Cirugía de la Mano, 2019)
Objective Delayed reconstruction of the articular surface of the distal radius after trauma is a difficult problem for hand surgeons, and the common solution is usually partial or total wrist fusion, relieving pain but sacrificing motion. A relative novel reconstructive technique addresses the problem with a free microvascular osteochondral flap, using the 3rd metatarsal (3MT) bone. We investigate the possibility of using the same donor as a graft rather than a free flap.Methods This was a prospective clinical study of patients with isolated lunate facet damage following trauma who underwent surgery to remove the damaged articular surface and in whom the defect was reconstructed with an osteochondral graft from the base of the 3MT. All of the patients were followed-up at specific time intervals, with pre- and postoutcome measures taken, including pain, grip strength, range of motion (ROM), and postoperative radiographs and computed tomography (CT) scans to evaluate graft resorption and union. Only patients with isolated distal radius defects were included.Results The average follow-up period was of 51 months (range: 14–73 months). The results of 7 patients included an average improvement of the pain score in the visual analogue scale (VAS) by 3 points, with an average arc of motion of 135°. In all, there was radiographic evidence of full incorporation of the graft, with no resorption. Donor site morbidity was minimal.Conclusions The current gold standard for distal radius articular surface reconstruction remains a free 3MT osteochondral flap. However, our results using the base of the 3MT as a graft shows promise, and if further follow-up confirms comparable results to the free flap technique, this would mean an easier and equally robust reconstruction without complicated microsurgery.Level of Evidence Therapeutic, Level V case series.
Keywords: metatarsal; reconstruction; distal radius